Expression profile analysis within the human hippocampus: Comparison of CA1 and CA3 pyramidal neurons - Ginsberg, Stephen D.; Che, Shaoli (Journal of comparative neurology (1911), 2005)
The hippocampus contains several distinct cell types that are interconnected by a well‐characterized series of synaptic circuits. To evaluate molecular and cellular signatures of individual cell types within the normal adult human hippocampal formation, expression profile analysis was performed on individual CA1 and CA3 pyramidal neurons using a novel single cell RNA amplification methodology coupled with custom‐designed cDNA array analysis. Populations of CA1 and CA3 neurons were also compared with regional dissections of the hippocampus from the same tissue sections. Molecular fingerprint comparison of cresyl violet–stained CA1 and CA3 pyramidal neurons microaspirated from the hippocampus of normal control subjects indicated significant differences in relative expression levels for approximately 16% (20 of 125) genes evaluated on the custom‐designed cDNA array platform. Significant differences were observed for several transcripts relevant to the structure and function of hippocampal neurons, including specific glutamate receptors, γ‐aminobutyric acid (GABA) A receptors, cytoskeletal elements, dopamine receptors, and immediate‐early genes. Compared with the regional assessment of gene expression, both CA1 and CA3 neurons displayed a relative enrichment of classes of transcripts that included glutamate receptors, transporters, and interacting proteins, GABA receptors and transporters, synaptic‐related markers, and catecholamine receptors and transporters. In contrast, the regional hippocampal dissection had an increased level of gene expression for cytoskeletal elements as well as glial‐associated markers. Expression profile analysis illustrates the importance of evaluating individual cellular populations within a functional circuit and may help define elements that confer unique properties to individual populations of hippocampal neurons under normal and diseased conditions. J. Comp. Neurol. 487:107–118, 2005. © 2005 Wiley‐Liss, Inc.